1999
DOI: 10.1177/154193129904300321
|View full text |Cite
|
Sign up to set email alerts
|

A User Decision Model for the Evaluation of the Human Computer Interface

Abstract: This paper discusses a dynamic model of the user's interaction with the user computer interface. It addresses how the user's decision processes interact with different levels of complexity in the user interface. Cellular automata are used to model the interaction of user decision schema and user computer interfaces. The user's decision schema determine the navigation through the interface. Users with idiosyncratic decision schema can effectively navigate only simple interfaces while users with data analytic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It eliminates DECISION STYLE ANALYSIS Decision style analysis consists of three components, a model of decision styles, a model of the system being analyzed, and a simulation in which the decision style model is applied in an iterative fashion to the system model. Previous work showed that the different real world behaviors of managers can be modeled (McGrew 1999(McGrew , 1998(McGrew , 1996. This work showed that a manager's behavior is consistent over time and situations, and described manager's decision styles.…”
Section: Why It Workmentioning
confidence: 99%
See 3 more Smart Citations
“…It eliminates DECISION STYLE ANALYSIS Decision style analysis consists of three components, a model of decision styles, a model of the system being analyzed, and a simulation in which the decision style model is applied in an iterative fashion to the system model. Previous work showed that the different real world behaviors of managers can be modeled (McGrew 1999(McGrew , 1998(McGrew , 1996. This work showed that a manager's behavior is consistent over time and situations, and described manager's decision styles.…”
Section: Why It Workmentioning
confidence: 99%
“…The results showed that the idiosyncratic decision makers preferred low complexity user interfaces and performed sub-optimally in the game situation. The data analytic decision makers could use both simple and complex user interfaces and could performed optimally in the game situation (McGrew 2002,1999, Wolfram 1994.…”
Section: Determining Decision Stylesmentioning
confidence: 99%
See 2 more Smart Citations